KEPASTIAN HUKUM TERHADAP PELAKU TINDAK PIDANA DELIK BIASA YANG DISELESAIKAN DENGAN MEDIASI ( STUDI KASUS KECELAKAAN LALU LINTAS YANG MENYEBABKAN KEMATIAN) - Abdullah, Jamal; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Traffic accident often causes the accident both small or big scales, the small scale causes light injury while the death. It is ruled in Article 310 of the Act Number 22, 2009 regarding the Traffic and Land Transportation states that the settlement of the violation of the act is done through litigation. However, there is the settlement outside the court in the level of investigation by the police by restitution given by the violator to the victim that can be material or immaterial form. The settlement of non-litigation is not recognized in the criminal law but it can be found in the society.Traffic accident with caused the death of an ordinary offense, not a complanit based offense. In a sense, the law enforcement officers or police remains under an obligation to process the case even though no report of casualties and others, and even if the perpetrator and the victim’s family has made peace efforts, but the legal process continues.Keywords: criminal act - traffic accident - mediation